The application value of lactate dehydrogenase in gynecological malignant tumors - Huang, Yanzhen; Zhang, Wenhao; Hao, Jue; Zhu, Ruizhen (Frontiers in Oncology, 2026)
Lactate dehydrogenase (LDH) is the key enzyme catalyzing the interconversion between pyruvate and lactate, playing an indispensable role in cellular glycolysis. Five isoenzymes of this enzyme exist in the human body, each exhibiting distinct tissue distribution patterns and biological functions. Recent studies indicate that LDH isoenzyme LDHA exhibits significantly elevated expression in gynecological malignancies. Within the tumor microenvironment, cancer cells frequently endure hypoxic conditions. To counter this stress and satisfy the heightened energy requirements associated with rapid proliferation and invasion, cancer cells have to undergo a comprehensive reprogramming of their metabolic pathways, with notable changes observed in glucose metabolism. Multiple studies confirm that LDH expression levels are clearly associated with tumor proliferation, invasive metastasis capacity, clinical prognosis and chemotherapy sensitivity. Targeting LDHA inhibition effectively suppresses cancer cell growth. However, this strategy has yet to achieve clinical translation. The paper aims to systematically summarize the expression characteristics, molecular regulatory mechanisms, and clinical correlations of LDH in common gynecological malignancies. And explores the potential value of LDH as a novel diagnostic biomarker and therapeutic target.